Optimizing User Experience through Analysis of the User Activity Patterns - Danilova, Olga (2021)
The User Experience has gained a lot of interest in the Web development world lately. The need to hear the user during the process of application design and development has become obvious. It is a general practice of the leading software solutions nowadays to apply agile solutions in the development process and center the design around the user. The possibility to achieve user centered design without direct interaction with the user group is a challenge, which can be met by using the user activity patterns for learning the User Experience with the application indirectly. Server logs can be a sufficient source of data for such research. An opportunity to learn User Experience from the User Activity patterns, emphasise the need to hear the user and learn from the user, a chance to present a solution for reducing the gap between the developer and the end user are the key goals of the given study.